Isoprostanes in Veterinary Medicine: Beyond a Biomarker - Ashley K. Putman; G. Andres Contreras; Lorraine M. Sordillo (MDPI AG, 2021)
Oxidative stress has been associated with many pathologies, in both human and animal medicine. Damage to tissue components such as lipids is a defining feature of oxidative stress and can lead to the generation of many oxidized products, including isoprostanes (IsoP). First recognized in the early 1990s, IsoP are formed in numerous biological fluids and tissues, chemically stable, and easily measured by noninvasive means. Additionally, IsoP are highly specific indicators of lipid peroxidation and thereby are regarded as excellent biomarkers of oxidative stress. Although there have been many advancements in the detection and use of IsoP as a biomarker, there is still a paucity of knowledge regarding the biological activity of these molecules and their potential roles in pathology of oxidative stress. Furthermore, the use of IsoP has been limited in veterinary species thus far and represents an avenue of opportunity for clinical applications in veterinary practice. Examples of clinical applications of IsoP in veterinary medicine include use as a novel biomarker to guide treatment recommendations or as a target to mitigate inflammatory processes. This review will discuss the history, biosynthesis, measurement, use as a biomarker, and biological action of IsoP, particularly in the context of veterinary medicine.